Corporate value creation - Karlson, Lawrence C. (John Wiley & Sons, Inc., 2015)
Corporate Value Creation provides an operations framework that management can use to optimize the impact decisions have on creating value by growing revenue and profitability. Designed to assist professionals without a strong business or financial education, this book provides a thorough understanding of the qualitative and quantitative aspects of managing a business for the purpose of value creation. Readers will find detailed information on financial reports, valuation, modeling and forecasting, and more, including discussion of best practices that functional management can embrace to leverage performance. The final chapter reviews key concepts and helps the reader tie them all together by using a step-by-step approach to build or modify a business plan that includes a complete set of financial statements. In addition, each chapter includes case studies or exercises so that the reader can practice using the material covered in the chapter